Diplomatic History of the Great Patriotic War and the New World Order - A. Y. Borisov (Vestnik MGIMO-Universiteta, 2015)
From ancient times, war was called "the creator of all things". And winners created the postwar world order. The article reveals the backstage, the diplomatic history of the Great Patriotic War, which make the picture of the main events of the war, that culminated in victory May 1945 in the capital of the defeated Third Reich, complete. The decisive role of the Soviet Union and its armed forces in the defeat of Nazi Germany and its allies was the strong foundation on which to build the strategy and tactics of Soviet diplomacy during the war. It was implemented in the course of negotiations with the Western Allies - the United States and Britain, led by President Roosevelt and Prime Minister Churchill. World history teaches, large and small wars have been fought on Earth for centuries for specific political interests. In this context, the Second World War has been a shining example not only to curb the aggressor states, the liberation of peoples from the Nazi tyranny, but also an attempt by the victor to organize a new, better postwar world order to guarantee a durable and lasting peace based on the cooperation of the allied states. But the allies in the war did not become allies in the organization of the postwar world. Their collaboration briefly survived the end of hostilities and was overshadowed start turning to the Cold War. It was largely due to the US desire to realize their material advantages to the detriment of the Soviet Union after the war and build a system that would be a one-sided expression of the interests of Washington. Americans, especially after the death of President Roosevelt, and during his successor Truman understood international cooperation as an assertion of its global leadership while ignoring the interests of the Soviet Union, which bore the brunt of the war.